How the Concept of Dignity Is Relevant to the Study of Energy Poverty and Energy Justice - Grossmann, Katrin; Trubina, Elena (Frontiers in Sustainable Cities, 2021)
Since the concept of energy poverty first emerged, studies have combined normative orientations, analytical approaches and policy review to engage with energy deprivation as a problematic feature of contemporary societies. Over the past decade, this scholarship has aimed to conceptualize the normative grounds for critique, empirical work and policy design when engaging with the interplay of social life and energy systems. Scholars now include dynamic and complex concepts such as energy vulnerability and energy deprivation and are shifting towards the incorporation of social-philosophical justice concepts. However, in most of these writings on energy equality or energy justice, material aspects like access to (clean) energy, affordable energy costs, and material deprivation are in the foreground. This resonates with the energy poverty literature’s emphasis on energy poverty as a material deprivation (Longhurst and Hargreaves 2019). The way that energy poverty can result in financial stress, cold homes, poor health and the need to cut other basic expenditures is well explored, but the less tangible, non-material deprivations stemming from energy poverty are less well captured. We instead find it beneficial to also focus on the less tangible, non-material deprivations which have not yet been captured conceptually, and argue that the concept of dignity can be a pathway to investigate them. We aim to demonstrate how “dignity” can add to the normative orientations of energy research, and complement existing frames. With an empirical position in Europe, we will draw from own empirical data and existing literature to illustrate how households living in energy poverty, or being cut off from energy provision, experience dignity violations.